(untitled) (Journal of Economic Additions, 2025)
This study aims to highlight the current state and future prospects of renewable energies, and to examine the alternatives for energy transition in Algeria. It also seeks to identify the obstacles and challenges that hinder the optimal utilization and benefit of these resources, with a focus on the national energy transition program and various proposed future strategies. The study concludes that renewable energies are a pressing issue of our time, necessitating a shift toward renewable resources as an alternative to conventional energy, especially given Algeria’s significant potential in this field. However, there remain certain challenges and constraints that limit their optimal exploitation in the country. Keywords: Renewable energy; traditional energy; energy transition; national energy transition program. Jel Classification Codes: Q2, Q26.